2016
DOI: 10.1172/jci87366
|View full text |Cite
|
Sign up to set email alerts
|

Dual CD19 and CD123 targeting prevents antigen-loss relapses after CD19-directed immunotherapies

Abstract: Potent CD19-directed immunotherapies, such as chimeric antigen receptor T cells (CART) and blinatumomab, have drastically changed the outcome of patients with relapsed/refractory B cell acute lymphoblastic leukemia (B-ALL). However, CD19-negative relapses have emerged as a major problem that is observed in approximately 30% of treated patients. Developing approaches to preventing and treating antigen-loss escapes would therefore represent a vertical advance in the field. Here, we found that in primary patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
424
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(449 citation statements)
references
References 63 publications
6
424
1
9
Order By: Relevance
“…The main mechanism of the toxicity and side effects could be attributed to cytokine release, tumor cell lysis, B-cell aplasia, and macrophage-activation syndrome. 26,27 Although most mild toxicity and side effects are reversible, some severe toxicities need medical treatment. A low dose of engineered cells may not trigger a response of antitumor activity, and an extra dose of immunotherapeutic cells may lead to severe toxicity and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanism of the toxicity and side effects could be attributed to cytokine release, tumor cell lysis, B-cell aplasia, and macrophage-activation syndrome. 26,27 Although most mild toxicity and side effects are reversible, some severe toxicities need medical treatment. A low dose of engineered cells may not trigger a response of antitumor activity, and an extra dose of immunotherapeutic cells may lead to severe toxicity and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Rearrangement in the mixed lineage leukemia (MLL) gene has also been described to contribute to the switch to a CD19-negative lineage following CAR T-cell therapy [57]. Strategies to overcome this include using 2 CAR constructs with different antigen specificity, for example CD19/CD123 [58]. Zah et al [59] recently reported on the development of a bispecific CD19/CD20 CAR construct with increased anti-tumor effect and prevention of CD19-negative ALL outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…A different kind of relapse was reported by clonal expansion of CD19-negative B cells after treatment with CD19-CARtransduced autologous T cells after allogeneic umbilical cord blood transplantation [71]. In fact, a high number of relapsed patients after CD19-CAR therapy show a CD19-negative phenotype of the blasts [72] indicating that mono-targeting approaches will have limitations in a significant proportion of patients. Preclinical data indicate superior tumor reactivity using a dual-expressing CAR construct comprising a CD19-and a CD123-CAR targeting the interleukin-3 receptor α chain [72].…”
Section: Adoptive Transfer Of Car-transgenic T Cells In the Context Omentioning
confidence: 99%
“…In fact, a high number of relapsed patients after CD19-CAR therapy show a CD19-negative phenotype of the blasts [72] indicating that mono-targeting approaches will have limitations in a significant proportion of patients. Preclinical data indicate superior tumor reactivity using a dual-expressing CAR construct comprising a CD19-and a CD123-CAR targeting the interleukin-3 receptor α chain [72]. CD123 is characteristically expressed also in a variety of other hematological malignancies [73].…”
Section: Adoptive Transfer Of Car-transgenic T Cells In the Context Omentioning
confidence: 99%